The Sinews of Habsburg power Lower Austria in a fiscal-military state 1650-1820 - Godsey, William D. 1964- (Oxford University Press, 2018)
The Sinews of Habsburg Power traces the development of the central European Habsburg monarchy into one of early modern Europe's leading powers. In particular, it looks to the domestic foundations of that power, which were upheld by the growth of a permanent standing army